2021
DOI: 10.1038/s41598-021-98995-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet diversity and environment determine the intestinal microbiome and bacterial pathogen load of fire salamanders

Abstract: Diverse communities of symbiotic microbes inhabit the digestive systems of vertebrates and play a crucial role in animal health, and host diet plays a major role in shaping the composition and diversity of these communities. Here, we characterized diet and gut microbiome of fire salamander populations from three Belgian forests. We carried out DNA metabarcoding on fecal samples, targeting eukaryotic 18S rRNA of potential dietary prey items, and bacterial 16S rRNA of the concomitant gut microbiome. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 95 publications
(90 reference statements)
2
21
0
Order By: Relevance
“…This seems a probable explanation for the observed prey richness among samples from Ons sampled during autumn. Relatively few arachnid (Arachnida) and centipede (Chilopoda) taxa were identified among our samples, although they have been reported in the diets of salamanders [15,22], suggesting an absence either among our samples or in local abundance.…”
Section: Coi Metabarcoding For Salamanders' Diet Characterizationmentioning
confidence: 71%
See 4 more Smart Citations
“…This seems a probable explanation for the observed prey richness among samples from Ons sampled during autumn. Relatively few arachnid (Arachnida) and centipede (Chilopoda) taxa were identified among our samples, although they have been reported in the diets of salamanders [15,22], suggesting an absence either among our samples or in local abundance.…”
Section: Coi Metabarcoding For Salamanders' Diet Characterizationmentioning
confidence: 71%
“…However, in many of these cases, often only a few prey taxa could be identified, because of either digestion or low taxonomic resolution. Our study identified 58 different prey taxa from three populations at variable taxonomic resolutions-fewer than the 76 prey taxa identified by gastric inspection from a higher number of individuals (N = 72), localities (N = 10), and a wider environmental and ecological survey [15], but nearly threefold more than from previous taxonomic assignment using DNA metabarcoding of 18S across three forest populations in Belgium [22]. Thus, DNA metabarcoding of COI increases taxonomic resolution and provides a cost-effective and expedient method for characterizing the diets of salamanders.…”
Section: Coi Metabarcoding For Salamanders' Diet Characterizationmentioning
confidence: 83%
See 3 more Smart Citations